CGIAR Excellence in Breeding Platform - Plan of Work and Budget 2021 - CGIAR Excellence in Breeding Platform (CGIAR Excellence in Breeding Platform, 2021)
The CGIAR Excellence in Breeding (EiB) Platform is accelerating the modernization of crop breeding programs that serve farmers in low- and middle-income countries. To combat hunger, poverty and climate change, farmers need diverse and continually improving crop varieties. Drawing on public and private sector innovations, EiB partners with breeding programs to deliver system-level coordination, shared services, expert guidance, resources, and access to cutting-edge technologies and practices.